1992
DOI: 10.1530/jrf.0.0960415
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of insulin-like growth factor I and gonadotrophins on relaxin and progesterone secretion by ageing corpora lutea of pigs

Abstract: Summary. Insulin-like growth factor I (IGF-I) is involved in paracrine/autocrine regulation of gonadal steroidogenesis and peptide hormone biosynthesis. This study was designed to determine whether IGF-I alone, or an interaction of IGF-I, is involved in augmenting the actions of luteinizing hormone (LH) and prolactin in controlling relaxin and progesterone secretion from ageing corpora lutea of hysterectomized gilts at days 110, 113 and 116 after oestrus. Luteal tissue slices were incubated for 8 h with IGF-I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
3
5
0
Order By: Relevance
“…Agreeing with our findings, IGF-1 and IGF-2 stimulated progesterone production in bovine luteal cells in vitro [21,22,57]. IGF-1 treatment resulted in a dose-dependent rise in basal progesterone production by mid-cycle bovine luteal cells [58], and consistent results were obtained from cow [21], pig [59], rat [14], rabbit [60], and human [61] in which IGF-1 alone, and in combination with gonadotropins, enhanced progesterone production by cultured luteal cells. In bovine CL, IGFs were effective in releasing progesterone and its stimulation was greatest during late luteal phase (15-18 days) [22].…”
Section: Discussionsupporting
confidence: 83%
“…Agreeing with our findings, IGF-1 and IGF-2 stimulated progesterone production in bovine luteal cells in vitro [21,22,57]. IGF-1 treatment resulted in a dose-dependent rise in basal progesterone production by mid-cycle bovine luteal cells [58], and consistent results were obtained from cow [21], pig [59], rat [14], rabbit [60], and human [61] in which IGF-1 alone, and in combination with gonadotropins, enhanced progesterone production by cultured luteal cells. In bovine CL, IGFs were effective in releasing progesterone and its stimulation was greatest during late luteal phase (15-18 days) [22].…”
Section: Discussionsupporting
confidence: 83%
“…This is in agreement with the results of Nicholson et al (1999) who showed that IGF-I is produced within the porcine CL and suggested an autocrine/paracrine role in CL development/function during the early luteal phase. A stimulatory effect of IGF-I on luteal progesterone production in vitro was noted by Huang et al (1992) in the pig. Our results are in agreement with data reported by Gadsby et al (1996) who discovered that IGF-I mRNA expression in small luteal cells was significantly greater before day 12 (days 4-10) than after day 12 (day 12-16) and are in accordance with subsequent data of Schams et al (1999) and Ge et al (2000) who detected IGF-I receptor in the pig CL, especially during the early luteal phase.…”
Section: Discussionmentioning
confidence: 96%
“…However, it is still unclear what factor(s) regulate the expression of RLN mRNA in the boar testis. Treatment of intact boars with hCG has been reported to have little effect on circulating levels of RLN detectable by RIA, although it induces testosterone secretion (Juang et al 1996), but there is evidence that LH and prolactin increase RLN production by porcine CL in vitro (Huang et al 1992), while prolactin maintains RLN secretion for 10 days in hypophysectomised-hysterectomised gilts (Li et al 1989). Thus, there may be marked differences in the factors regulating RLN gene expression between Leydig cells and CL cells.…”
Section: Discussionmentioning
confidence: 99%